Approximation from the Humanist Administration in a Case Study of Hotels in Villa De Leyva, Boyacá - TÉLLEZ-BEDOYA, Carlos Arturo; GÓMEZ-RODRÍGUEZ, Dustin Tahisin; RAMOS-PINEDA, Camilo Andres; BERNAL-RODRÍGUEZ, Edgar Andrés (Journal of Environmental Management and Tourism; Vol 11 No 2 (2020): JEMT Volume Xi Issue 2(42) Spring 2020, 2020)
Purpose: To learn about the interpretations that the internal actors of the hotels in Villa de Leyva have about business management, in the context of the humanist administration. Design: Based on qualitative research, a descriptive study was addressed. Methodology: The method used was the case study applied to a non-probabilistic sample of three organizations in order to get an approximation of the social reality and in this way, identify the management styles that are developed in the hotels of the municipality of  Villa de Leyva, Boyacá . In this context, the information was collected through in-depth interview technique. Findings: It was evidenced that, most of Villa de Leyva hotels develop practices that are far from the humanist administration, this is why, it would have greater relevance to apply this type of postulates to improve the competitiveness and projection of this type of organizations, as well as, the stability and happiness of employees. Originality of the research: This research is a pioneer in the Boyacá region. The results show perceptions in the context of these hotels about the humanist administration, which, unfortunately, is not always taken into account.